An insight into growth transition in AlN epitaxial films produced by metal-organic chemical vapour deposition at different growth temperatures. (January 2022) - Sahar, M.A.A.Z. Md; Hassan, Z.; Ng, S.S.; Hamzah, N.A.; Yusuf, Y.; Novikova, N.N.; Yakovlev, V.A.; Klimin, S.A.
Abstract: This work demonstrates a clear picture growth transition of aluminium nitride (AlN) films from the three-dimensional (3D) to the two-dimensional (2D) regime on the sapphire substrate at various temperatures using metal-organic chemical vapour deposition (MOCVD) under low reactor pressure. The high deposition rate of large 3D AlN islands that isolated each other change to 2D growth mode with a smoother surface as temperature increases from 800 °C to 1340 °C. From x-ray diffraction measurement, the AlN (100), AlN (002), and AlN (101) planes exhibit strong peak monocrystalline AlN (002) films as the temperature increase. It found that the AlN film grew at 1100 °C in the Frank–van der Merwe or 2D growth mode exhibits the highest crystalline quality with the threading dislocation density around 2.21 × 10 9 cm −2 . In addition, the lattice vibrational parameters of the AlN films at 1100 °C shows the lowest phonon damping from IR spectra results. Thus, this study details the AlN epitaxial films growth transition, which is crucial for growing high crystalline quality AlN layer using the MOCVD technique. Highlights: AlN thin films transition from 3D to 2D as the growth temperatures increase at lower reactor pressure. The smoothest surface was observed at a higher growth rate but not at a higher growth temperature. The intermediate growth temperature produced the high-quality AlN thin films under Frank–van der Merwe or 2D growth mode. Theoretical modelling of the infrared reflection spectrum reveals a stressed layer between AlN film and sapphire substrate.